Learning of Flame Test using Low Cost Experiment - Meena, O. P.; Sharma, R. K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Flame test is most frequently used for qualitative analysis of some metal ions. In the flame test, samples in the form of paste with concentrated hydrochloric acid are introduced in a hot, non-luminous flame using platinum wire and the color of flame is observed. The characteristic color of the flame reliably gives information about the presence of a particular metal ion present in the sample. Platinum is a costly metal and therefore, the cost of experimentation is high. However, continuous laboratory practices of flame test have evolved some new experimental procedures without platinum wire. These experiments are easy to perform and low cost is attractive feature of them. In the present study a low cost flame test was identified from the literature and it was introduced in the practical sessions of B.Sc. B.Ed. Part-I students. Usefulness and impact of the low cost experiment on learning of students was studied and results of the study have been complied in the form of present research paper